The customers' consumption trends on healthy ice cream / Nik Fakrulhazri Nik Hassan ... [et al.] - Nik Hassan, Nik Fakrulhazri; Ahmad, Noorazlina; Abu Kassim, Abd Razak; Hamzah, Yusnita (Universiti Teknologi MARA, Perlis, 2021)
Ice cream is a favorite dessert for many societies around the world. Eating ice can increase the feeling of fun, enjoyment as well as happiness to individuals. As such, not only it is loved by the youngsters, it is also loved by the elders. A good average calorie for ice cream is approximately 200 kcal/100g. However, adding more sugar into the ice cream for consumption beyond the limit may cause several health diseases such as obesity, diabetes, and even organ failures. In Malaysia, its ice cream market had increased from RM 795.9 million in 2017 to 3.43 per cent in 2018. Putting the increasing trend and health risks into the equation, to ensure that ice cream remains enjoyable by people of all age groups and health backgrounds, the creation of a healthy ice cream formula is necessary. This empirical study investigated customer consumption trends on healthy ice cream, assessed customer perception and proposed a marketing strategy to promote the consumption of healthy ice cream. This study had successfully developed a customer consumption trends profile on healthy ice cream and assisted local marketers to design marketing strategies on healthy ice cream "brands" in Malaysia.